Q: 6u2 plus 7u plus 5 3u - 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2u + 1 = 5u + 5 2u - 5u = 5 - 1 -3u = 4 3u = -4 u = -4/3

0.2

T - U = 3T = 2U + 1(2U + 1) - U = 3U + 1 = 3U = 2T = 2U + 1 = 5The number is 52.

(1/8) / (u/6) = 6u/8 = 3u/4

13

Related questions

3u plus 1/10 when solved give the value of u = 1/30.

2u + 1 = 5u + 5 2u - 5u = 5 - 1 -3u = 4 3u = -4 u = -4/3

0.2

T - U = 3T = 2U + 1(2U + 1) - U = 3U + 1 = 3U = 2T = 2U + 1 = 5The number is 52.

(1/8) / (u/6) = 6u/8 = 3u/4

-5u + 4 + 8u = 43simplify by subtracting 4 from both sides of the equation to get rid of the 4 on the left:-5u + 8u = 43Simplify further by combining the -5u and the 8u:3u = 43Divide both sides by 3 to solve for u:u = 43/3rewrite the fraction:u = 14 1/3

14

It is 35.

13

9

1

8